Superficial femoral artery thrombosis after midshaft femoral fracture fixation with an intramedullary nail: a case report - Rubenandran, Ramachandran; Sanjiv, Rampal; Prema, Sivalingarajah; Kee, Tan Eng; Devaraj, Navin Kumar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Intramedullary nailing is the preferred method of closed shaft fracture fixation of long bones. One of the most dreaded complications to occur following internal fixation of a lower limb fracture is pseudo- or false aneurysm which can lead to the loss of the limb due to acute ischemia. This diagnosis is made by contrast angiogram of the limb. Pointers to the diagnosis include absent distal limb pulsation as well as other signs of acute ischemia post trauma or surgery. We present a case of development of pseudo-aneurysm in an elderly patient following open reduction and internal fixation of a femoral fracture. This case report outlines a prompt multidisciplinary approach of management in a rare case of pseudoaneurysm post fixation of long bone.